2010
DOI: 10.1380/ejssnt.2010.84
|View full text |Cite
|
Sign up to set email alerts
|

Optical Second Harmonic Generation from Periodic Steps on Rutile TiO2(110)

Abstract: We have succeeded in observing optical second harmonic generation (SHG) from steps on the TiO2 surfaces adsorbed with HCOOH. The samples were single crystals of rutile TiO2 with (110), (15 15 4), (13 9 0), and (671) faces. These samples underwent annealing in O2 gas, HF etching, and immersion into HCOOH aqueous solution to adsorb HCOOH molecules on their surfaces. Their surfaces were characterized by reflection high energy electron diffraction (RHEED) and atomic force microscopy (AFM), and were confirmed to ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…3. As already reported in our earlier work,35 the annealed sample surface is made up of multilayer step bunches (>10 ML) and flat (110) terraces [Fig. 3(a)].…”
mentioning
confidence: 65%
See 3 more Smart Citations
“…3. As already reported in our earlier work,35 the annealed sample surface is made up of multilayer step bunches (>10 ML) and flat (110) terraces [Fig. 3(a)].…”
mentioning
confidence: 65%
“…Our previous rotational SHG measurement for TiO 2 (110) at the SHG photon energy of 4.66 eV showed that quadrupole bulk SHG from the (110) face is almost at the noise level for the nearly normal incidence. 35 Analogously, the corresponding bulk contribution from the vicinal (110) face in question is expected to be as small. In fact, the clearly different SFG responses between annealed and unannealed TiO 2 (15 15 4) in Fig.…”
Section: B Near-gap Local Density Of States Of the Step Bunches On Amentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous work,21 we succeeded in detecting the signals of the steps periodically aligned on the TiO 2 surfaces selectively by means of second harmonic generation (SHG)13–20 with nearly normal incident fundamental excitation. We found that both high index TiO 2 (15 15 4) and (671) surfaces with steps have large nonlinear susceptibility elements $\chi_{xxx}^{(2)}$ and $\chi_{xyy}^{(2)}$ , with x representing the [0 0 1] and y representing the [1 1 0] directions.…”
Section: Introductionmentioning
confidence: 99%